On G-derivations of Lie–Yamaguti superalgebras - Abdaoui, Meher; Boujelben, Jamel (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.5 Let G be an automorphism group. We study G-derivations associated with the Lie–Yamaguti superalgebras. The concept of G-derivation, which is a derivation under both bilinear and trilinear operations is defined for the Lie–Yamaguti superalgebras. We also study some important properties of G-derivations, as well as with their relationship with other derivations of the Lie–Yamaguti superalgebras.